INTERPRETATION OF PSYCHOLOGICAL IDEAS IN THE WORKS OF ABU HAMID AL-GHAZALI AND SIGMUND FREND (Eureka Journal of Humanities and Social Research, 2026)
Innate factors that govern him are in line with Sigmund Freud's view that"man is born with innate aggression and sexual desire, manruled byness." Freud said that the conscious processes that make up a person represent a part of the psyche, while unconsciousness occupies a large part of the basis.According to Abu Hamid al-Ghazali, man is born with the forces of lust, anger, lust and chastity. These ideas of al-Ghazali are an oriental view of the theories of the Western scholar Z. Freud
Keywords: Lust, anger, chastity, lust, iceberg